Modifiable Cardiovascular Risk Factors in Patients With Sporadic Cerebral Cavernous Malformations: Obesity Matters - Chen, Bixia; Saban, Dino; Rauscher, Steffen; Herten, Annika; Rauschenbach, Laurèl; Santos, Alejandro; Li, Yan; Schmidt, Boerge; Zhu, Yuan; Jabbarli, Ramazan; Wrede, Karsten H.; Kleinschnitz, Christoph; et al. (Stroke (1970), 2021)
This study aims to assess the influence of modifiable cardiovascular risk factors on hemorrhage risk of sporadic cerebral cavernous malformations (CCMs). From 1219 consecutive CCM patients (2003-2018), adult subjects with sporadic CCM and complete magnetic resonance imaging were included. We evaluated presence of intracerebral hemorrhage (ICH) as mode of presentation, occurrence of ICH during follow-up and risk factors arterial hypertension, diabetes, hyperlipidemia, nicotine abuse, and obesity (body mass index >30 kg/m ). Impact of risk factors on ICH at presentation was calculated using univariate and multivariate logistic regression with age and sex adjustment. We performed Kaplan-Meier and Cox regression to analyze cumulative 5-year risk for (re)bleeding. We included 682 patients with CCM. The univariate logistic regression showed a significant relationship (odds ratio=1.938 [95% CI, 1.120-3.353], =0.018) between obesity and ICH as mode of presentation. Multivariate adjusted logistic regression confirmed significant correlation with odds ratio=1.902 (95% CI, 1.024-3.532, =0.042). Cox regression did not identify predictors for occurrence of (re)hemorrhage ( >0.05; hazard ratios: arterial hypertension 1.112 [95% CI, 0.622-1.990], diabetes 0.850 [95% CI, 0.208-3.482], hyperlipidemia 0.719 [95% CI, 0.261-1.981], nicotine abuse 1.123 [95% CI, 0.591-2.134], and obesity 0.928 [95% CI, 0.416-2.070]). This study provides evidence that obesity may be a risk factor for CCM hemorrhage. It was significantly associated with ICH as mode of presentation. Other risk factors (arterial hypertension, diabetes, hyperlipidemia, and current nicotine abuse) showed no such effect. None of the factors showed to be independent predictors for cumulative 5-year risk of (re)bleeding.